2005
DOI: 10.2527/2005.83122876x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray-dried animal plasma and immunoglobulins on performance of early weaned pigs1,2

Abstract: Five experiments were conducted to evaluate the effects of dietary spray-dried porcine plasma (SDPP) and spray-dried bovine plasma (SDBP) and their various molecular weight fractions on performance of pigs weaned at approximately 14 or 21 d of age. In addition, the efficacy of various levels of the immunoglobulin G (IgG)-rich fraction of SDPP and SDBP were evaluated. Experiment 1 evaluated the dietary addition of SDPP and three of its fractions (IgG-rich, albumin-rich, and low molecular weight fractions). Pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 13 publications
(20 reference statements)
11
130
2
7
Order By: Relevance
“…Contrary to our original hypotheses, the children's growth was not affected by consumption of either BSC or MMN. Previous studies found that BSC increased dietary intakes and rates of weight gain of domesticated farm animals, possibly because the IgG contained in the preparation reduced the incidence of infections (Weaver et al, 1995;Pierce et al, 2005). We are not aware of any relevant prior studies of BSC and growth in humans.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to our original hypotheses, the children's growth was not affected by consumption of either BSC or MMN. Previous studies found that BSC increased dietary intakes and rates of weight gain of domesticated farm animals, possibly because the IgG contained in the preparation reduced the incidence of infections (Weaver et al, 1995;Pierce et al, 2005). We are not aware of any relevant prior studies of BSC and growth in humans.…”
Section: Discussionmentioning
confidence: 91%
“…Experimental trials in newly weaned farm animals have demonstrated that incorporation of spray-dried bovine or porcine blood plasma into their feeds increases their dietary intakes and produces greater rates of weight gain compared with control diets (Weaver et al, 1995;Pierce et al, 2005), possibly because the higher concentrations of immunoglobulins in the plasma-fortified products protected against infection. We therefore proposed that similar benefits might occur in young children in populations that experience high rates of diarrhea and other infections.…”
Section: Introductionmentioning
confidence: 99%
“…0.05) by dietary treatment, they suggested that SDPP and SDAP contain specific anti-ETEC antibodies, which is one of the factors responsible for its superior growth-enhancing effects in the presence of pathogen challenge. Pierce et al (2005) conducted a comprehensive study examining the effects of dietary SDPP, SDBP (spray-dried bovine plasma), porcine Ig and bovine Ig in healthy, earlyweaned piglets and showed that all Ig preparations resulted in higher growth rates. They concluded that the improved growth performance was due to a nutrient-sparing effect as a result of the action of the consumed Ig.…”
Section: Discussionmentioning
confidence: 99%
“…All diets exceeded the recommended nutrient requirement levels for the growing rat for all nutrients (National Research Council, NRC, 1995). The FDOI and IOI fractions were included in the respective diets at a concentration approximately equal to the amount of spray-dried porcine plasma (SDPP) IgG used in previous studies (Pierce et al, 2005;Balan et al, 2009 Values for nutrients were from chemical analysis except for carbohydrate that was calculated by difference using the formula (100 2 (moisture 1 ether extract 1 ash 1 CP) 5 carbohydrate).…”
Section: Experimental Dietsmentioning
confidence: 99%
“…Spray-dried animal plasmas are characterised by a rich protein content, whose digestibility and amino acid composition are similar to those of the proteins in sow's milk (van Dijk et al, 2001), and whose Igs content can represent 24% to 25% (Niewold et al, 2007). Plasma from both bovine and porcine origins seem efficient in improving performances of piglets, and the IgG fraction would appear to be the main component responsible for the growth-promoting properties for these products (Pierce et al, 2005). The Igs may prevent viruses and bacteria from interacting with the gut wall, resulting in an improvement of gut function (Coffey and Cromwell, 2001).…”
Section: Gallois Rothkö Tter Bailey Stokes and Oswaldmentioning
confidence: 99%